2022
DOI: 10.18502/ijph.v51i12.11455
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Hyperuricemia in Cardiac Patients with Post-Contrast Acute Kidney Injury (PC-AKI) and Different Basic Renal Functions: A Meta-Analysis

Abstract: Background: Uric acid level has shown a certain relationship with the incidence of post-contrast acute kidney injury (PC-AKI), whereas it remains controversial whether hyperuricemia can function as a predictor of PC-AKI in patients with different basic creatinine serum level. The present meta-analysis aimed to investigate whether hyperuricemia is an independent risk factor for PC-AKI and to explore the relationship between hyperuricemia and basic renal function. Methods: Relevant studies were retrieved v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The pooled analysis indicated that PC-AKI occurrence was significantly higher in the hyperuricemic group than in the normouricemic group (20.62% versus 13.05%). Hyperuricemia was accompanied by an increase in the incidence risk of PC-AKI (OR: 2.48; 95% CI: 1.77-3.46%) (37). In a meta-analysis in 2017, Kanbay et al assessed the pathogenic role of uric acid in CI-AKI and found that higher levels of SUA, as described by the authors, were associated with a 2-fold increase in the risk of AKI occurrence (pooled OR: 2.03; 95% CI: 1.48-2.78) (38).…”
Section: Discussionmentioning
confidence: 99%
“…The pooled analysis indicated that PC-AKI occurrence was significantly higher in the hyperuricemic group than in the normouricemic group (20.62% versus 13.05%). Hyperuricemia was accompanied by an increase in the incidence risk of PC-AKI (OR: 2.48; 95% CI: 1.77-3.46%) (37). In a meta-analysis in 2017, Kanbay et al assessed the pathogenic role of uric acid in CI-AKI and found that higher levels of SUA, as described by the authors, were associated with a 2-fold increase in the risk of AKI occurrence (pooled OR: 2.03; 95% CI: 1.48-2.78) (38).…”
Section: Discussionmentioning
confidence: 99%